Informed consent in cluster randomised trials: a guide for the perplexed - Nix, Hayden P; Weijer, Charles; Brehaut, Jamie C; Forster, David; Goldstein, Cory E; Taljaard, Monica (BMJ open, 2021)
In a cluster randomised trial (CRT), intact groups—such as communities, clinics or schools—are randomised to the study intervention or control conditions. The issue of informed consent in CRTs has been particularly challenging for researchers and research ethics committees. Some argue that cluster randomisation is a reason not to seek informed consent from research participants. In fact, systematic reviews have found that, relative to individually randomised trials, CRTs are associated with an increased likelihood of inadequate reporting of consent procedures and inappropriate use of waivers of consent. The objective of this paper is to clarify this confusion by providing a practical and useful framework to guide researchers and research ethics committees through consent issues in CRTs. In CRTs, it is the unit of intervention—not the unit of randomisation—that drives informed consent issues. We explicate a three-step framework for thinking through informed consent in CRTs: (1) identify research participants, (2) identify the study element(s) to which research participants are exposed, and (3) determine if a waiver of consent is appropriate for each study element. We then apply our framework to examples of CRTs of cluster-level, professional-level and individual-level interventions, and provide key lessons on informed consent for each type of CRT.